Unveiling unselective fishing in China: A nationwide meta‐analysis of multispecies fisheries - Sun, Ming; Li, Yunzhou; Chen, Yong (Fish and fisheries (Oxford, England), 2023)
Understanding and managing fishery selectivity to target species and desirable size are instrumental to fisheries management. China, as the world's largest producer of marine capture fisheries, has been widely perceived to possess unselective domestic fisheries. To date, this perception remains largely anecdotal and conjectural, hindering the development of evidence‐based and effective management solutions. Here, we conducted a literature review to examine the magnitude and scale of unselective fisheries in China. By collating and analysing 140 fishery‐level and 807 species‐level records from 66 peer‐reviewed publications from 2010 to 2021, we found that primary target species were absent in 59% of fisheries, while unidentifiable low‐value and juvenile mixed catch were universal. Key commercial taxa were subject to nationwide multi‐gear and multispecies fisheries, each involving an average of 3.33 types of gear and accounting for less than 25% of catch individually. The ‘permissible gears’ defined by the national gear regulatory catalogue were selective over target species and caught negligible by‐products, though they were used less frequently, representing only 24% of catch records. While unselective fishing can provide seafood supplies for China's large population and potentially facilitate balanced harvest, management actions are needed to control the fishing pressure on primary target species and by‐product species. Amid the ongoing fisheries management reform in China, we proposed management recommendations tailored to China's needs and social contexts, including accounting for the trade‐off between socio‐economic and ecological goals, contemplating impacts of unselective fishing when implementing TAC programmes, and strengthening fisheries monitoring to inform management at multiple scales.